2017
DOI: 10.1021/acsami.7b04916
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Translocation of Nanoemulsions via Oral Delivery

Abstract: The in vivo translocation of nanoemulsions (NEs) was tracked by imaging tools with an emphasis on the size effect. To guarantee the accurate identification of NEs in vivo, water-quenching environment-responsive near-infrared fluorescent probes were used to label NEs. Imaging evidence confirmed prominent digestion in the gastrointestinal tract and oral absorption of integral NEs that survive digestion by enteric epithelia in a size-dependent way. In general, reducing particle size leads to slowed in vitro lipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 57 publications
3
43
0
Order By: Relevance
“…The microscopic size of the aggregates was evident from DLS as well as the milky appearance of the emulsion. Xia et al (28) demonstrated that smaller nanoemulsions (∼100 nm) distribute to enterocytes and basolateral tissues and larger nanoemulsions (∼1,000 nm) adhered to villi. Larger particles were also shown to exhibit 2-fold lower bioavailability than smaller particles.…”
Section: Discussionmentioning
confidence: 99%
“…The microscopic size of the aggregates was evident from DLS as well as the milky appearance of the emulsion. Xia et al (28) demonstrated that smaller nanoemulsions (∼100 nm) distribute to enterocytes and basolateral tissues and larger nanoemulsions (∼1,000 nm) adhered to villi. Larger particles were also shown to exhibit 2-fold lower bioavailability than smaller particles.…”
Section: Discussionmentioning
confidence: 99%
“…The area under the plasma concentration-time curve (AUC 0→ 8 ) of PFs-SMEDDS NR was remarkably higher than that of the PFs-suspension. The relatively enhanced bioavailability of PFs-SMEDDS NR may be attributed to the enhanced drug absorption by improving the solubility and membrane permeability of the poorly soluble drugs in the gastrointestinal tract [ 32 , 33 ]. After oral administration, SMEDDS spontaneously form tiny emulsion droplets with a diameter of ˂100 nm under physiological temperature and gastrointestinal peristalsis.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, far more work should be carried out to resolve those questions. Apart from FRET and SAXS, other techniques have been used or might be used to study the fate of nanoparticles in the GI tract, such as cryo-TEM, near-infrared fluorescent dye, the water-quenching environment-responsive fluorescent probes, quantum dot and aggregation-induced emission (AIE) 18 , 31 ( Fig. 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microemulsions coated with a dense PEG shell significantly avoid the hindrance of mucus, and several mucus-penetrating microemulsions have been reported 27 , 28 , 29 . Moreover, some reports demonstrated that partially intact lipid-based nanoparticles diffuse through the mucus layer, including the intestinal epithelium 30 , 31 . However, it worth noting that the intermediate phases will be inevitably affected by the mucus layer when passing through mucus, and the performance should be dependent on their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%